Efficient inhibition of murine breast cancer growth and metastasis by gene transferred mouse survivin Thr34→Ala mutant - Peng, Xing-Chen (BioMed Central, 2008)
BACKGROUND: Metastasis in breast cancer is a vital concern in treatment because most women with primary breast cancer have micrometastases to distant sites at diagnosis. As a member of the inhibitor of apoptosis protein (IAP) family, survivin has been proposed as an attractive target for new anticancer interventions. In this study, we investigated the role of the plasmid encoding the phosphorylation-defective mouse survivin threonine 34→alanine mutant (Msurvivin T34A plasmid) in suppressing both murine primary breast carcinomas and pulmonary metastases. METHODS: In vitro study, induction of apoptosis by Msurvivin T34A plasmid complexed with cationic liposome (DOTAP/Chol) was examined by PI staining fluorescence microscopy and flow cytometric analysis. The anti-tumor and anti-metastases activity of Msurvivin T34A plasmid complexed with cationic liposome (DOTAP/Chol) was evaluated in female BALB/c mice bearing 4T1 s.c. tumors. Mice were treated twice weekly with i.v. administration of Msurvivin T34A plasmid complexed with cationic liposome (DOTAP/Chol), PORF-9 null plasmid complexed with cationic liposome (DOTAP/Chol), 0.9% NaCl solution for 4 weeks. Tumor volume was observed. After sacrificed, tumor net weight was measured and Lung metastatic nodules of each group were counted. Assessment of apoptotic cells by TUNEL assay was conducted in tumor tissue. Microvessel density within tumor tissue was determined by CD31 immunohistochemistry. Alginate-encapsulated tumor cells test was conducted to evaluate the effect on angiogenesis. By experiment of cytotoxicity T lymphocytes, we test whether Msurvivin T34A plasmid complexed with cationic liposome (DOTAP/Chol) can induce specific cell immune response. RESULTS: Administration of Msurvivin T34A plasmid complexed with cationic liposome (DOTAP/Chol) resulted in significant inhibition in the growth and metastases of 4T1 tumor model. These anti-tumor and anti-metastases responses were associated with triggering the apoptosis of tumor cells directly, inhibiting angiogenesis and inducing specific cellular immune response. CONCLUSION: The present findings suggest that the Msurvivin T34A plasmid complexed with cationic liposome may provide an effective approach to inhibit the growth and metastases of a highly metastatic mouse breast cancer model with minimal side effects.